Rekonstruksi Teologi Radikalisme di Indonesia, Menuju Islam Rahmatan Lil Alamin - Asmani, Jamal Mamur (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2017)
AbstractReligious radicalism nowaday has became a major world threat. Religious radicalism has been able to indoctrinate people until they commit extremist acts that may harm other and leads into series, including life and wealth. The process of religious radical indoctrination comes from the claim of exclusive truth. Where they believed, Islam and its understanding is one, that is what they understood and practice during the life of the prophet Muhammad SAW.Jihad is understood as jihad with the soul and property by taking up arms to quell extinguish kufr and polytheism on earth. The slogan Isy Kariman or mut syahidan (noble life or martyrdom) encourage them to quell any disobedience. Tolerating kufr and polytheism considering as allowing infidelity threatened with great punishment. The only way to overcome infidelity through mobilizing all possible capabilities and means for the glory of Islam.This theology their soul is contrary to the spirit of diversity, as one important ideology for the Indonesian society and also contrary to the philosophy of Islam as a religion that bring mercy to all human kind. Qur'an in many places assert that faith is the right prerogative of god cannot be interfered with anyone, so that a person is forbidden to hate others because of differences in beliefs. Prophet Muhammad SAW. set a good example when lead humanity in Madina by issuing the Charter of Medina.The Charter of Medina who inspire and motivate Walisongo to preach Islam as a peaceful, tolerant and progressive, not by violence, intimidation, threats, and justifies any means. History proved, Walisongo is method of islamic propagation have proven as an effective way to convert many millions of Java heterogeneous and pluralistic. Although Hinduism and Buddhism are already secure hegemony, but through gentleness, modesty, and exemplary Walisongo, Islam have penetrated into life of into massive islamic conversion, without any compulsion, threat on intimidation. This is the implementation as Islam rahmatan lil'Alamin that become true characteristic of the spirit as plural and heterogeneous society. Depart, from this context, there should be urgent needs to reconstruct fundamentalist ideologies of exclusiveness, through major strategic theological steps.Keywords: radicalism, Islam, rahmatan lil'Alamin, reconstruction, tolerant